THE EFFECTIVENESS OF CHEST PHYSIOTHERAPY WITH TRIPOD AND FOWLER POSITION TO INCREASING OXYGEN SATURATION - Manurung, Sondang; Zuriati, Zuriati; Dewi, Nani Asna; Setiawan, Cepy; Rachmat, Annisa (Universitas Islam Negeri Alauddin Makassar, 2021)
Chronic Obstructive Pulmonary Disease (COPD) is one of the three leading causes of death in the world in low and middle income countries up to 90%, characterized by airway obstruction making it difficult for the body to transport sufficient oxygen. This study examines chest physiotherapy with a tripod and Fowler's position in oxygen saturation. Quantitative analysis using quasi-experimental method and two-group pre-test-posttest design with 50 samples using accidental sampling technique. Statistical test using unpaired t test showed a significant difference in average oxygen saturation using a tripod position with a P-Value of 0.00. The tripod position showed better results as indicated by the increase in oxygen saturation from 93.40 to 97.64 compared to the Fowler position which increased from 92.64% to 95.52. Therefore, this study suggests chest physiotherapy using a tripod position is more effective in increasing oxygen saturation in COPD patients. This intervention can remove secretions, help reduce shortness of breath in patients, and affect the value of increasing oxygen saturation in COPD patients. This non-pharmacological action is a nursing intervention based on scientific evidence for independent nursing actions in providing nursing care to COPD patients